Identification of Plant Growth promoting Rhizobacteria (PGPR) from Revegetated Soils of Lignite Mines of Neyveli, Tamilnadu - LINNETT NAVEENA. M; S. UMA GOWRIE (International Journal of Pharma and Bio Sciences, 2018)
Identification of PGPR from disturbed soil ecosystem such as mine spoil dumps can prove to be useful in enhancing plant growth during reclamation process of mine soil by revegetation. In this study, 25 bacterial isolates were obtained from Leucaena leucocephala (V.N-Subabul, Leguminosae) found in Neyveli Lignite Mines and screened for their plant growth promoting traits like production of Siderophore, Indole acetic acid, HCN and Ammonia. The tolerance of the isolates to heavy metals like mercury, chromium and cobalt at different concentrations was also tested. Results indicated that there are various genera of bacteria demonstrating growth promoting activities, the predominant genera being Bacillus sp. Production of IAA ranged between 30-80 µg/ml in the presence of tryptophan and siderophore production was noted in 64% of the total bacterial isolates. Ammonia production was reported in 72% of isolates and 44% of isolates proved positive for HCN production. The only isolate NL-9 which tolerated the heavy metal mercury was identified as Lysinibacillus fusiformis based on 16 S rRNA sequencing. The Minimum Inhibitory Concentration (MIC) of mercury for NL-9 was determined as 100 ppm. The MIC of cobalt was found to be 100 ppm for nine isolates and 150 ppm for sixteen isolates. Chromium exerted least toxicity against the isolates as evident by the high MIC value of 300 ppm.